Aspectos fenológicos, morfoanatômicos, bioquímicos e ecofisiológicos de Copernicia alba (Morong ex Morong & Britton) em ambiente alagado e não alagado - Araujo, Maicon Marinho Vieira (2018)
Considered one of the largest floodplains on the planet, the Mato Grosso Pantanal is subject to rainfall changes, with periods of flooding and drought. This flood pulse governs its hydroecological functioning, conferring particular biogeochemical and ecological characteristics that sustain vital environmental conditions for the establishment and development of the vegetal species that coexist there. About 2,000 plant species live in the Pantanal, but only 18% are found in flooded and non-flooded environments. One representative of these species is Copernicia alba, a palm of great regional importance, especially for the production of wood and waxes, besides representing the second largest area of monodominant formation of the Pantanal. Thus, C. alba was chosen to help elucidate, through phenological, morphoanatomical, biochemical and agronomic studies, the adaptive mechanisms of the plant in environments with different water pressures. Phenological aspects were obtained by means of biweekly observation of 22 individuals between August 2015 and August 2017. C. alba showed a perennial behavior, with flowering during the dry season and greater leaf intensity during the transition between the rainy season and dry. There was synchrony between the period of fruiting and dispersion of the seeds. The incidence of floral buds occurred in the dry period, with intense flowering in the transition between dry and rainy season. The fruiting period occurred only during the rainy season. The fruit of carandá is a drupe, ranging from ellipsoid to round, of black color and presents perianto persistent. The endocarp is rigid, dark brown and opaque. The seed is hemipteral, globose to ovoid shape. The tegument is thin, externally adhered to the endocarp and endosperm, being formed by three overlapping cell layers, rich in phenolic compounds. The fruits are rich in carbohydrates and present seeds with high oil contents. The water uptake by the C. alba seeds follows a three - phase pattern, presenting a protrusion of the cotyledonary petiole between 168 and 480 hours and 264 and 480 hours for those from the non - flooded and flooded environment, respectively. Seeds originating from flooded environment remain with high germination rates, producing healthy seedlings, both in sawdust + sand substrate and in water. Whereas those from non-flooded environment have a significantly lower germination rate; caused by rotting of the radicle. For the evaluation of plant growth, as well as potential gas exchange, substrates composed of the mixture of soil and organic residues based on chicken litter and bovine manure were used. A commercial and soil substrate with NPK was also used. It was possible to identify that the commercial substrate promoted the greatest development of the seedlings and that the presence of organic matter and mineral nutrients in the substrate of cultivation are important in the production of C. alba seedlings.